1998
DOI: 10.1093/oxfordjournals.aje.a009456
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Omega-3 and Omega-6 Fatty Acid Content and Breast Cancer in the EURAMIC Study

Abstract: The fatty acid content of adipose tissue in postmenopausal breast cancer cases and controls from five European countries in the European Community Multicenter Study on Antioxidants, Myocardial Infarction, and Cancer (EURAMIC) breast cancer study (1991 -1992) was used to explore the hypothesis that fatty acids of the omega-3 family inhibit breast cancer and that the degree of inhibition depends on background levels of omega-6 polyunsaturates. Considered in isolation, the level of omega-3 or omega-6 fat in adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(49 citation statements)
references
References 47 publications
0
45
1
3
Order By: Relevance
“…The ratio of n-6 to n-3 PUFA (OMR) in animal fats may make an important contribution to human health although it is not clear whether these are all direct effects or whether they are partial effects due to food overconsumption and obesity. Several studies have shown that a high OMR in tissues or cholesteryl-esters is associated with several diseases including cancers such as prostate, bowel and breast cancer, CVD, autoimmune diseases and inflammatory diseases such as rheumatoid arthritis and inflammatory bowel disease (Godley et al 1996;Harvei et al 1997;Gogos et al 1998;Simonsen et al 1998;Yang et al 1999c;Simopoulos 2008;Murff et al 2011). Intake of many types of fat have been examined, with a suggestion of a threshold of n-6 PUFA, and reduced rates of disease for fats or oils low in n-6 PUFA, including animal fat (Zock and Katan 1998;Freedman et al 2008;Alexander et al 2010;Brennan et al 2010;Dong et al 2011;Gilsing et al 2011;Liu et al 2011;Psaltopoulou et al 2011;Chajes et al 2012).…”
Section: Components Of Animal Fat With Known Health Benefitsmentioning
confidence: 99%
“…The ratio of n-6 to n-3 PUFA (OMR) in animal fats may make an important contribution to human health although it is not clear whether these are all direct effects or whether they are partial effects due to food overconsumption and obesity. Several studies have shown that a high OMR in tissues or cholesteryl-esters is associated with several diseases including cancers such as prostate, bowel and breast cancer, CVD, autoimmune diseases and inflammatory diseases such as rheumatoid arthritis and inflammatory bowel disease (Godley et al 1996;Harvei et al 1997;Gogos et al 1998;Simonsen et al 1998;Yang et al 1999c;Simopoulos 2008;Murff et al 2011). Intake of many types of fat have been examined, with a suggestion of a threshold of n-6 PUFA, and reduced rates of disease for fats or oils low in n-6 PUFA, including animal fat (Zock and Katan 1998;Freedman et al 2008;Alexander et al 2010;Brennan et al 2010;Dong et al 2011;Gilsing et al 2011;Liu et al 2011;Psaltopoulou et al 2011;Chajes et al 2012).…”
Section: Components Of Animal Fat With Known Health Benefitsmentioning
confidence: 99%
“…A European multicentre study examining ratios of o3 to o6 fatty acids in adipose tissue in relation to breast cancer risk (Simonsen et al, 1998) found consistent inverse associations of the fatty acid ratios with breast cancer across most study centres (Kohlmeier, 1997). Two breast cancer studies that examined fatty acids in phospholipids (Chajès et al, 1999) and erythrocytes (Pala et al, 2001) suggest complex relations between diet, fatty acid and hormone metabolism, and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…skewed n-6:n-3 PUFA ratio in maize oil may be supportive of tumour growth or altered immune functions (Black et al 1992;Rose & Connolly, 1993;Simonsen et al 1998;Klein et al 2000;Furukawa et al 2002;Calder, 2003). The balance of n-6 and n-3 PUFA rather than the total amount of fat consumed may be more important in determining cancer risk.…”
Section: N-3 Fatty Acids and Palliation Of Cancer: Associated Symptommentioning
confidence: 99%